Edukasi kesehatan tentang alat kontrasepsi dalam rahim (KB AKDR) pada wanita usia subur - Wedharing Sekar Asmarani; Gunarmi Gunarmi; Zesika Intan Navelia (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The Intrauterine Device (IUD) is the most effective long-acting reversible contraceptive (LARC) method; however, its uptake remains low—including within the service area of ​​the Cisoka Community Health Center due to a lack of knowledge among women of reproductive age. Proper understanding is essential for these women to select and decide on the appropriate contraceptive method. A solid understanding helps increase knowledge, foster positive attitudes, and correct misconceptions regarding family planning methods. Purpose: To increase knowledge about IUD contraception among women of reproductive age as an effort to boost the number of family planning acceptors. Method: The activity was conducted on April 28, 2026, in the service area of ​​the Cisoka Community Health Center, Tangerang Regency, involving 30 respondents (women of reproductive age). A direct, participatory educational approach was employed, utilizing lectures supported by leaflets. Levels of knowledge and understanding were assessed using a one-group pretest-posttest design, with questionnaires administered before (pretest) and after (posttest) the educational session. Evaluation involved analyzing the aggregated questionnaire data and descriptively reporting the respondents' level of understanding regarding IUD contraception. Results: The results showed that the respondents' mean age was 34.03 years, with the majority (73.3%) falling within the 30–39 age range. Most respondents (63.3%) had a high school education, and the majority (73.3%) were housewives. Questionnaire analysis revealed an improvement in respondents' knowledge regarding IUD contraception: the proportion of respondents in the